E : Zeichnungen - Schafhausen, Nicolaus; Künstlerhaus Bethanien, Berlin (Berlin : Künstlerhaus Bethanien Berlin, 1993)
Althoff, Kai ; Burchill, Janet ; McCamley, Jennifer ; Davar, Katja ; Duwenhögger, Lukas ; Höller, Carsten ; Riedel, Susanne ; Slama, Torsten ; van der Stokker, Lily ; Trauttmansdorff, Octavian
E : Zeichnungen ausgewählt von Nicolaus Schafhausen, Künstlerhaus Bethanien, Berlin, 28. Mai bis 13. Juni 1993
boek